Investigation of Performance Parameters of Different Photovoltaic Cell Materials using the Lambert-W Function. (December 2016) - Dhass, A.D.; Lakshmi, P.; Natarajan, E.
Abstract: A photovoltaic (PV) system can generate electrical energy and maintain sustainability in the environment. In the future, these energy-generating systems that do not alter the environment will play a major role in building a nation. A PV system, a sustainable energy source, acts as a vital system in reducing environmental pollution and is called a clean energy source. In this study, we analysed the performance of various PV cell materials such as mono crystalline (m-Si), polycrystalline (p-Si), and black solar cells. The operating parameters of a solar PV cell, such as parasitic series and shunt resistances and photo-generated current, are affected by temperature. A m-Si module of 250 W shunt resistance, polycrystalline module of a 3-kW (Yingli's manufactured) system in a series resistance, and black m-Si type of 250 W and 3 kW of photo-generated current were highly influenced and changed their output with the effect of temperature. Theoretical parasitic resistances were calculated using the Lambert W function. These theoretical investigation results were compared with the experimental results of 3-kW polycrystalline solar PV modules. Moreover, the influence of this resistance on system performance was analysed.